Associations between number of consecutive night shifts and impairment of neurobehavioral performance during a subsequent simulated night shift - Michelle Magee; Tracey L Sletten; Sally A Ferguson; Ronald R Grunstein; Clare Anderson; David J Kennaway; Steven W Lockley; Shantha MW Rajaratnam (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVE: This study aimed to investigate sleep and circadian phase in the relationships between neurobehavioral performance and the number of consecutive shifts worked. METHODS: Thirty-four shift workers [20 men, mean age 31.8 (SD 10.9) years] worked 2-7 consecutive night shifts immediately prior to a laboratory-based, simulated night shift. For 7 days prior, participants worked their usual shift sequence, and sleep was assessed with logs and actigraphy. Participants completed a 10-minute auditory psychomotor vigilance task (PVT) at the start (~21:00 hours) and end (~07:00 hours) of the simulated night shift. Mean reaction times (RT), number of lapses and RT distribution was compared between those who worked 2-3 consecutive night shifts versus those who worked 4-7 shifts. RESULTS: Following 4-7 shifts, night shift workers had significantly longer mean RT at the start and end of shift, compared to those who worked 2-3 shifts. The slowest and fastest 10% RT were significantly slower at the start, but not end, of shift among participants who worked 4-7 nights. Those working 4-7 nights also demonstrated a broader RT distribution at the start and end of shift and had significantly slower RT based on cumulative distribution analysis (5^th, 25^th, 50^th, 75^th percentiles at the start of shift; 75th percentile at the end of shift). No group differences in sleep parameters were found for 7 days and 24 hours prior to the simulated night shift. CONCLUSION: A greater number of consecutive night shifts has a negative impact on neurobehavioral performance, likely due to cognitive slowing.